Pengaruh Pemanfaatan Quick Response Code Indonesian Standard (Qris) di Era Ekonomi Digital Terhadap Pelaporan Keuangan UMKM - Nabila Zalzabila (Dharma Ekonomi, 2025)
The utilization of Quick Response Code Indonesian Standard (QRIS) by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has an important role in encouraging digitalization of transactions and improving financial recording and reporting. The background of this study is the need for MSMEs to adapt to the development of digital payment technology, especially in the midst of accelerated digitization triggered by the COVID-19 pandemic. Although QRIS provides various benefits, such as ease of transactions and automatic recording, there are still a number of obstacles such as limited digital literacy, uneven infrastructure, and concerns related to cybersecurity, especially in remote areas. This study uses a qualitative method with a case study approach to SMEs that have adopted QRIS in several regions in Indonesia. Data were collected through field observations, and documentation studies related to the use of QRIS in business activities. Data analysis was conducted thematically to explore in-depth understanding of the experiences, challenges, and benefits felt by MSME actors in the use of QRIS. The results showed that QRIS makes it easier for MSMEs to process payments and automatic digital transaction recording, thereby increasing the accuracy and transparency of financial statements. However, limited access to electricity, digital devices, and digital security literacy are significant barriers to optimal implementation of QRIS. The security aspect of digital transactions is an important concern for MSMEs, who need further education and technical support. Thus, strengthening digital literacy, improving infrastructure, and strict cybersecurity regulations are urgently needed to encourage wider and inclusive adoption of QRIS among MSMEs in Indonesia.